2019
DOI: 10.1186/s13104-019-4382-1
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm and hemagglutinin formation: a Hallmark for drug resistant uropathogenic Escherichia coli

Abstract: Objective Urinary tract infection (UTI) is one of the most frequent disease encounters in pregnant mothers, and the most drug resistant, biofilm and hemagglutinin producer Uropathogenic Escherichia coli (UPEC) is the major etiologic agent. Therefore, the aim of this study was to assess the association between the antimicrobial resistance, and biofilm and hemagglutinin production of Uropathogenic Escherichia coli . Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…On the other hand, our results revealed that not only were the majority of ESBLs-producing and MDR isolates susceptible to imipenem, meropenem, and fosfomycin but susceptibility to amikacin, cefoxitin, and nitrofurantoin was also considerable. This finding is consistent with some previous reports from Iran and other countries [29,31]. As carbapenems are β-lactam antibiotics with high antibacterial activity, they are commonly used as first-line treatments for infections caused by ESBLs-producing Enterobacterales.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, our results revealed that not only were the majority of ESBLs-producing and MDR isolates susceptible to imipenem, meropenem, and fosfomycin but susceptibility to amikacin, cefoxitin, and nitrofurantoin was also considerable. This finding is consistent with some previous reports from Iran and other countries [29,31]. As carbapenems are β-lactam antibiotics with high antibacterial activity, they are commonly used as first-line treatments for infections caused by ESBLs-producing Enterobacterales.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the previous studies in Iran and other countries, in our results, 52.4 and 84.8% of UPEC isolates belonged to ESBLs-producing and MDR strains, respectively [27][28][29][30][31]. The prevalence of MDR isolates was higher than the pooled prevalence of MDR UPEC with 49.4% [32] and 65.8% [33] in Iran.…”
Section: Discussionsupporting
confidence: 91%